2020
DOI: 10.1002/jcp.30179
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of miR‐128 in musculoskeletal diseases

Abstract: MicroRNA-128 (miR-128) is associated with cell proliferation, differentiation, migration, apoptosis, and survival. Genetic analysis studies have demonstrated that miR-128 participates in bone metabolism, which involves bone marrow-derived mesenchymal stem cells, osteoblasts, osteoclasts, and adipocytes. miR-128 also participates in regeneration of skeletal muscles by targeting myoblast-associated proteins. The deregulation of miR-128 could lead to a series of musculoskeletal diseases. In this review, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 142 publications
1
12
0
Order By: Relevance
“…MiR-370-3p has been shown to down-regulate ACADSB gene expression and inhibit the formation of slow-twitch muscle fiber [ 40 ]. Additionally, some of the DEmiRs identified in our study, such as eca-miR-192, eca-miR-10a and eca-miR-128, are involved in muscle cell proliferation, differentiation and energy expenditure [ 41 , 42 , 43 ]. These results suggested that some DEmiRs identified in our study might also be involved in skeletal muscle fiber development and composition in donkeys.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-370-3p has been shown to down-regulate ACADSB gene expression and inhibit the formation of slow-twitch muscle fiber [ 40 ]. Additionally, some of the DEmiRs identified in our study, such as eca-miR-192, eca-miR-10a and eca-miR-128, are involved in muscle cell proliferation, differentiation and energy expenditure [ 41 , 42 , 43 ]. These results suggested that some DEmiRs identified in our study might also be involved in skeletal muscle fiber development and composition in donkeys.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) consist of 19–25 nucleotides and regulate gene expressions at the posttranscriptional level by binding to 3′UTRs of target mRNAs ( 12 ). Accumulating evidence points to an intimate connection between miRNAs and bone metabolism, keeping balanced by osteoblastic bone formation and osteoclastic bone resorption ( 12 , 13 ). However, the studies about the action mechanisms of miRNAs on GIOP are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR-199b-5p, miR-10a-5p, miR-10b-5p, miR-24-1-5p, miR-223-3p, and miR-338-3p was suppressed, whereas miR-291a-5p, miR-125b-1-3p, and miR-291b-5p expression was enhanced (Table 3, Ref. [100][101][102][103][104][105][106][107][108]) (Fig. 2).…”
Section: Micrornas That Regulate Osteoclastogenesis and Osteoresorptionmentioning
confidence: 94%
“…Numerous studies have shown that miR-128 is involved in the regulation of signaling pathways associated with osteoclastogenesis [102,109] and with reactive oxygen species, inflammation, and fibrosis in many tissue types [109]. In HK2 cells, miR-128-3p was shown to inhibit apoptosis and inflammation by targeting the TGFBR2 gene [110].…”
Section: Micrornas That Regulate Osteoclastogenesis and Osteoresorptionmentioning
confidence: 99%